Changing trends in prognostic factors for patients with multiple myeloma after autologous stem cell transplantation during the immunomodulator drug/proteasome inhibitor era. Issue 2 (6th February 2015) - Takamatsu, Hiroyuki; Honda, Sumihisa; Miyamoto, Toshihiro; Yokoyama, Kenji; Hagiwara, Shotaro; Ito, Toshiro; Tomita, Naoto; Iida, Shinsuke; Iwasaki, Toshihiro; Sakamaki, Hisashi; Suzuki, Ritsuro; Sunami, Kazutaka
<x xml:space="preserve">Abstract</x> We evaluated the clinical significance of prognostic factors including the International Staging System (ISS) and modified European Group for Blood and Marrow Transplantation response criteria in 1650 Japanese patients with multiple myeloma (MM) who underwent upfront single autologous stem cell transplantation (ASCT). We categorized patients into two treatment cohorts: pre‐novel agent era (1995–2006) and novel agent era (2008–2011). The combined percentage of pre‐ASCT complete response and very good partial response cases (463 of 988, 47%) significantly increased during the novel agent era compared with the pre‐novel agent era (164 of 527, 31%; P < 0.0001). The 2‐year overall survival (OS) rate of 87% during the novel agent era was a significant improvement relative to that of 82% during the pre‐novel agent era (P = 0.019). Although significant differences in OS were found among ISS stages during the pre‐novel agent era, no significant difference was observed between ISS I and II (P = 0.107) during the novel agent era. The factors independently associated with a superior OS were female gender (P = 0.002), a good performance status (P = 0.024), lower ISS (P < 0.001), pre‐ASCT response at least partial response (P < 0.001) and ASCT during the novel agent era (P = 0.017). These results indicate that the response rate and OS were significantly improved, and the ISS could not clearly stratify the prognoses of Japanese patients with MM who underwent upfront single ASCT during the novel agent era.